Clevidipine for Perioperative Blood Pressure Control in Infants and Children - Sergio D. Bergese; David B. Tulman; Joseph D. Tobias (MDPI AG, 2013)
Various pharmacologic agents have been used for perioperative BP control in pediatric patients, including sodium nitroprusside, nitroglycerin, β-adrenergic antagonists, fenoldopam, and calcium channel antagonists. Of the calcium antagonists, the majority of the clinical experience remains with the dihydropyridine nicardipine. Clevidipine is a short-acting, intravenous calcium channel antagonist of the dihydropyridine class. It undergoes rapid metabolism by non-specific blood and tissue esterases with a half-life of less than 1 minute. As a dihydropyridine, its cellular and end-organ effects parallel those of nicardipine. The clevidipine trials in the adult population have demonstrated efficacy in rapidly controlling BP in various clinical scenarios with a favorable adverse effect profile similar to nicardipine. Data from large clinical trials regarding the safety and efficacy of clevidipine in children is lacking. This manuscript aims to review the commonly used pharmacologic agents for perioperative BP control in children, discuss the role of calcium channel antagonists such as nicardipine, and outline the preliminary data regarding clevidipine in the pediatric population.